Community Initiatives in Preventing Youth Gang Fights in Padang City: A Case Study of the Anti Brawl Task Force in Tanjung Saba Pitameh Nan XX Subdistrict - Tunggara, Rayhan Owen; Sasmita, Siska (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze community initiatives in preventing youth brawls in Padang City through a case study of the Anti-Brawl Task Force in Tanjung Saba Pitameh Nan XX Village. This research uses a qualitative approach with a case study method. Data were collected through observations, in-depth interviews, and documentation, with informants consisting of community leaders, members of the Anti-Brawl Task Force, village officials, and security personnel. Data analysis was performed using the interactive model by Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions, with data validity tested through source and technique triangulation. The results show that the community initiative in preventing brawls is dominated by the Locality Development model, as proposed by Rothman (2001), reflected in the active participation and collective awareness of the community in maintaining neighborhood security through patrols, monitoring vulnerable areas, and using a persuasive approach with youth. The Social Planning model serves as a supporting element through the identification of brawl patterns, determination of high-risk times and locations, and coordination with relevant authorities, although it is not supported by systematic and written planning. Meanwhile, the Social Action model has not developed significantly because the approach used is more cooperative than confrontational. These findings emphasize that community-based brawl prevention is more effective when built through participation, solidarity, and local community independence.